Online Self-Presentation Strategies and Fulfillment of Psychological Needs of Chinese Sojourners in the United States - Yang, Tian; Ying, Qianwei (Frontiers in Psychology, 2021)
This study statistically analyzed survey data to examine the relationship between fulfillment of psychological needs of 223 Chinese sojourners in the United States and their online self-presentation strategies on Chinese and American social media. The results showed that the combined use of proactive and defensive self-presentation strategies on Chinese social media instead of American social media were more effective to fulfill the sojourners’ need for autonomy. Moreover, presentation strategies that helped to meet the sojourners’ need for relatedness were significantly different between Chinese and American social media. Specifically, a proactive strategy was more effective to meet sojourners’ need for relatedness on Chinese social media, while a defensive strategy was more effective to fulfill their need for relatedness on American social media.